Relationship between body mass index and blood pressure in school students - Sunil Kumar Jena; Madhuchhanda Pattnaik (Wolters Kluwer Medknow Publications, 2018)
Background: Children of school age group in developing countries are facing the problem of overweight and obesity because of lifestyle change, playing video games, watching television as well as consuming energy rich diet. Childhood obesity continues as obesity in adulthood. The chance of high blood pressure (BP) in overweight and obese children is more than healthy weight children. Objectives: (i) Effect of body mass index (BMI) on BP. (ii) Association of overweight and obesity with hypertension (HTN). Materials and Methods: This study included 580 students of age group 6-12 years of both boys and girls. All students were from English medium school. Measurement of height and weight was done by standard procedure. BMI was calculated by weight and height. BP measurement was done by auscultatory method. Statistical analysis was done by SPSS 16. Results: Overweight and obesity were more in boys than girls. There was significantly more BP in overweight and obese participants than healthy weight individuals. There was positive correlation between BMI and BP both systolic and diastolic BP. Prevalence of HTN in boys is more than the girls. Odds ratio suggested that overweight and obesity was associated with HTN. Conclusion: This study concludes that overweight and obese school students were prone to develop elevated BP and HTN and hence were prone to cardiovascular risk.